(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The concept of any teacher is, first of all, his personal understanding of how it is necessary to educate, train and develop children. The pedagogical concept, in my opinion, should in no case be DISCONNECTED from the reality in which each individual child receives his upbringing and education. And it absolutely does not matter what subject the teacher teaches, be it natural science subjects or humanities. The main thing is that the teacher can achieve his most important goal - to educate a person with healthy moral principles, who is not only capable of setting the necessary goals, but also achieving them.